EXPLORING THE ARTISTRY OF PHONETIC STYLISTIC DEVICES IN LANGUAGE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article provides an insightful exploration of phonetic stylistic devices, elucidating their role in enhancing the depth, rhythm, and emotive resonance of language. Beginning with an introduction to key phonetic devices such as alliteration, assonance, consonance, onomatopoeia, and rhyme, it delves into their distinctive functions in shaping written and spoken expression. The article adeptly illustrates how these devices transcend mere linguistic tools, serving as potent instruments for writers, poets, advertisers, and orators to captivate audiences and evoke emotions. The piece goes beyond a mere enumeration of devices, delving into their cultural significance across languages and literary traditions. It aptly highlights the diverse usage of phonetic devices, acknowledging their varied prominence in different linguistic contexts and historical periods. Notably, it underscores the influence of phonetic devices in speeches, literature, marketing, and everyday communication, emphasizing their universal relevance.